Evaluación nutricional e indicadores bioquimicos en jóvenes universitarios de la provincia de Sánchez Carrión, región La Libertad - González-Siccha y Cols., Anabel Doris (2019)
Objective: To determine the nutritional evaluation and biochemical indicators in university students of the Province of Sánchez Carrión, La Libertad Region. Material and Method: Descriptive, cross-sectional study and prospective. Participants 29 young people (26 women and 03 men), 17-29 years of both sexes, inhabitants of Huamachuco. Prior to being included in the study, signed informed consent was required. It was determined the anthropometric measures using variables: weight (Kg), height (cm) and mass index bodily. Blood samples were taken by puncture of the finger pulp, hemoglobin was determined (method Cyanomethamoglobin) and   hematocrit (microcentrifugation). Results: The average values ​​were hemoglobin = 15.99 ± 1.74; hematocrit = 47.73 ± 3.48, BMI = 23.66 ± 3.78; age 19.07 ± .2.45. They had normal BMI 72.42%, overweight 24.14% and obesity 3.45% that could be due to overnutrition and diet rich in carbohydrates 62.07% had high hemoglobin with normal BMI (44.83%), overweight (13.79%), obesity (3.45%), and 31.03% with normal hemoglobin, without statistical significance (x2 = 0.684, P> 0.05, the group of 17-20 years of female sex had 62.07% high Hb (physiological polycythemia), but age does not influence the Hb concentration. (x2 = 5.151; P> 0.05) but if the sex (x2 = 5.59; P <0.05). 68.96% presented hematocrit elevated with normal BMI (55.17%), overweight (13.79%) and normal hematocrit (31.03%) without significance statistics (x2 = 3.192; P> 0.05). Of 68.96% with elevated hematocrit, the majority according to age group was 17-20 years (62.07%), (x2 = 0.787, P> 0.05) and according to sex was 58.62% women and 10.34% males (x2 = 1.487; P> 0.05). At high altitudes erythropoiesis is stimulated in compensation for the partial decrease of oxygen by elevating hemoglobin and hematocrit, called physiological polycythemia. It is concluded that, higher percentage of young people have high hemoglobin and hematocrit values ​​with normal BMI due to at high altitudes that stimulate erythropoiesis.